The analysis of the permeability process of calcium antagonists in developing transdermal forms with a cardiovascular effect - Tatyana Shyteyeva; Svitlana Gubar; Nataliia Smielova; Elena Bezchasnyuk; Liana Budanova (Pensoft Publishers, 2021)
Aim. The aim of the work was to evaluate the possibility of using calcium antagonists, namely, nifedipine and amlodipine besylate, while conducting transdermal delivery, that included the analysis of in vitro permeability process as a primary preformulation stage of pharmaceutical development of a transdermal dosage form, determination of qualitative and quantitative characteristics of a permeability process and the expediency analysis of development of a therapeutic transdermal system (TTS) with a cardiovascular effect. Materials and methods. The active pharmaceutical ingredients (API) of nifedipine and amlodipine besylate. The study has been carried out in vitro by a dialysis method using a modified diffusion device of the Valia-Chien design. Results. Character analysis, description of the mathematical model and definition of the kinetic parameters in the process of permeability of the studied medicinal products (MP) of nifedipine and amlodipine besylate allowed to evaluate their potential for creating TTS as being positive and appropriate. The implemented methodological approaches allow to substantiate the further algorithm for the development of cardiovascular TTS with the mentioned API.